Standardization of soaking conditions for soybean seeds/cotyledons for improved quality of soymilk - CHOPRA, RANJU; PRASAD, D N (The Indian Journal of Animal Sciences, 2013)
Actual time necessary for complete soaking of soybean seeds was studied. Soybean seeds/cotyledons were soaked in 0.25% solution of sodium bicarbonate at different temperatures. Optimum water uptake for seeds and cotyledons was 129.0 and 117.0% respectively. Extended soaking beyond this stage resulted in loss of soluble solids in soak solution. Rate of water uptake increased with increase in temperature, and declined with increase in soaking time. Minimum time required for complete soaking of seeds was 8,10,12 and 14 hr at 35°,30°,25° and 200e respectively. Maximum soaking time for cotyledons was only 2 hr at above temperature, but is not recommended for soymllk processing in view of flavour problems. The cotyledons can be directly blanched as per standard procedures.